Voltage regulation capability of a prototype Static VAr Compensator for wind applications - Boynuegri, A. R.; Vural, B.; Tascikaraoglu, A.; Uzunoglu, M.; Yumurtaci, R. (ELSEVIER SCI LTD, 2012)
Power quality of distribution networks is severely affected with the increasing of wind penetration in power systems. One of the most important considerations in grid integration of wind energy is voltage variations. This paper presents a prototype Static VAr Compensator (SVC) that considers RMS value of grid voltage power as reference for reactive power regulation of wind turbines in order to decrease voltage fluctuations. The simulation and experimental studies have demonstrated the effective influences of the SVC on the voltage profile, even in the case of the sudden changes in the voltage magnitude. Furthermore, the experimental results give fairly good agreements with the simulation results. (c) 2011 Elsevier Ltd. All rights reserved.
Keywords: Wind turbines; Static VAr Compensator; Voltage fluctuations; Voltage regulation; POWER QUALITY; TURBINES; FLICKER; FARMS; INSTALLATIONS; NETWORKS; DIPS; Energy & Fuels; Engineering